Papua New Guinea : Government, Economy and Society. - Howes, Stephen. (Pacific Series, 2022)
Edited by Professor Stephen Howes and Professor Lekshmi N. Pillai, Papua New Guinea: Government, Economy and Society is a must-read for students, policymakers and anyone interested in understanding this complex and fascinating country.